Should doctors talk to relatives without a competent patient’s consent? - Mytton, O. (Journal of medical ethics, 2005)
A view from a student: ethical teaching, based on ethical guidelines, is at odds with clinical practice. Is this poor practice, or is the ethical guidance too simple?